(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A semi-quantitative study was carried out on benthic foraminifera from beneath, within and above the Middle to Late Pleistocene sapropels S—9, S—8, S—7, S—6, S—5, in two Western Mediterranean and Calabrian Ridge cores, in order to investigate how stagnation conditions developed in the Eastern Mediterranean during the considered interval.